Knowledge, attitudes and practices of Australian dairy goat farmers towards the control of gastrointestinal parasites - Endris A. Ali; Ghazanfar Abbas; Ian Beveridge; Sandra Baxendell; Berwyn Squire; Mark A. Stevenson; Abdul Ghafar; Abdul Jabbar (Parasites & Vectors)
Abstract Background Gastrointestinal parasites such as nematodes and coccidia are responsible for significant economic losses in the goat industry globally. An indiscriminate use of antiparasitic drugs, primarily registered for use in sheep and cattle, in goats has resulted in drug-resistant gastrointestinal parasites. Very little is known about the gastrointestinal parasite control practices used by Australian dairy goat farmers that are pivotal for achieving sustainable control of economically important parasites. The study reported here provides insights into gastrointestinal parasite control practices of Australian dairy goat farmers based on responses to an online survey. Methods The questionnaire comprised 58 questions on farm demography, husbandry and grazing management, knowledge of gastrointestinal parasites and their importance in dairy goats, diagnosis of infections, antiparasitic drugs and alternate control options. After a pilot survey (n = 15 respondents), a link to the questionnaire was available to all (n = 456) registered members of the Dairy Goat Society of Australia Ltd from 17 April to 16 June 2023. Multiple correspondence analyses (MCA) were performed to explore the association between selected parasite control practices. Results A total of 66 (14%) respondents completed the questionnaire. Of these, 74% (49/66) observed parasite-related illnesses in their goats; two-thirds of them assessed worms burden using faecal egg counts (FECs), with 26% (39/149) deworming their goats based on the results of the FECs. Most respondents (97%; 183/188) perceived that gastrointestinal parasites caused production losses and ranked Haemonchus contortus as the most important parasite. Anitparasitic drugs were used by 94% (62/66) of respondents, with the most frequently used anthelmintics being a commercial combination of four anthelmintics (levamisole, closantel, albendazole and abamectin), benzimidazoles and macrocyclic lactones. Most respondents (77%; 51/66) were unaware of anthelmintic resistance on their property. MCA results delineated two clusters of gastrointestinal parasites management. Conclusions This study provides insights into the demography of Australian dairy goat farms, the husbandry and grazing practices used by dairy goat farmers, their knowledge regarding gastrointestinal parasites and their practices for internal parasite control, thereby paving the way for tackling drug resistance in gastrointestinal parasites in dairy goats. Graphical Abstract